The information content of inflation swap rates for the long-term inflation expectations of professionals evidence from a MIDAS analysis - Hanoma, Ahmed Ragab Elsaid Abdelhamid; Nautz, Dieter (Freie Universität Berlin, 2018)
Long-term inflation expectations taken from the Survey of Professional Forecasters are a major source of information for monetary policy. Unfortunately, they are published only on a quarterly basis. This paper investigates the daily information content of inflation-linked swap rates for the next survey outcome. Using a mixed data sampling approach, we find that professionals account for the daily dynamics of inflation swap rates when they submit their long-term inflation expectations. We propose a daily indicator of professionals' inflation expectations that outperforms alternative indicators that ignore the high-frequency dynamics of inflation swap rates. To illustrate the usefulness of the new indicator, we provide new evidence on the (re-)anchoring of U.S. inflation expectations
Keywords: Geldpolitik; Strategische Planung; Inflation; Inflation Expectations Dynamics; Expectations Anchoring; MIDAS